2018
DOI: 10.1111/1467-8551.12314
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Hubris, Trade Associations and Regulatory Knowledge in Micro‐Firms

Abstract: To avoid breaking the law for regulatory non-compliance, it is essential that micro-firm owner-managers are aware of deficiencies in their knowledge, so that they can seek improvement and avoid over-confidence (i.e. hubris) in their knowledge levels. Using newly collected survey data from micro-firms in the English accommodation sector and multivariate techniques, the authors explore the possibility of hubris by making a novel distinction between the Perceived-Knowledge and Actual-Knowledge of regulation held … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 92 publications
(182 reference statements)
0
11
0
Order By: Relevance
“…One particular impact identified by prior research is the financial burden of adhering to regulations and associated influence on firms' behaviour (Bailey and Thomas, 2017). We posit such effects extend to what micro-firm owner-managers perceive to be relevant regulations, given extant literature on limited managerial knowledge and the risks of potential under/over-compliance (Cumming and Zambelli, 2013;Stokols et al, 2001;Betton et al, 2019). This burden includes both directly attributable cost increases to acquire/install required equipment and the wider impacts like time for research/understanding (FSB, 2004;Lewis et al, 2015aLewis et al, , 2015b.…”
Section: Micro-firms and Regulationmentioning
confidence: 95%
See 2 more Smart Citations
“…One particular impact identified by prior research is the financial burden of adhering to regulations and associated influence on firms' behaviour (Bailey and Thomas, 2017). We posit such effects extend to what micro-firm owner-managers perceive to be relevant regulations, given extant literature on limited managerial knowledge and the risks of potential under/over-compliance (Cumming and Zambelli, 2013;Stokols et al, 2001;Betton et al, 2019). This burden includes both directly attributable cost increases to acquire/install required equipment and the wider impacts like time for research/understanding (FSB, 2004;Lewis et al, 2015aLewis et al, , 2015b.…”
Section: Micro-firms and Regulationmentioning
confidence: 95%
“…Regulatory burden is widely considered to have a disproportionate effect on micro-firms because the costs/effects do not fully vary in proportion to firm size (Calcagno and Sobel, 2014;Carter et al, 2009;HM Government, 2013;OECD, 2001;Zorpas et al, 2008). Microfirms are hampered by their limited monetary/time resources, along with poor understanding of the relevant regulations and a lack of managerial skill (Carson, 1985;Johnson, 2002;Betton et al, 2019). For example, higher wage costs following an increase in the minimum wage for which the burden of compliance is at least partially fixed, therefore the overall costs/effects are a disproportionately greater percentage of revenue and managerial time for small-firms (Collard and Godwin, 1999;OECD, 2001).…”
Section: Micro-firms and Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…If intermediary BAs can rely on spontaneous or public-order sanctions, they are able to coordinate various forms of collective action. They can enable valuecreating transactions by spreading information about business partners and regulations (Betton et al, 2018;Cai − Szeidl, 2018;Johnson et al, 2002;Leonidou − Katsikeas, 1997;Pyle, 2005Pyle, , 2006bRecanatini − Ryterman, 2001), and about breaches of property rights (Pyle, 2011;Rochlitz, 2016). They can improve knowledge-sharing (Costa et al, 2017;Kirby, 1988;Luna − Tirado, 2008;Pyle, 2006a;Qiao et al, 2014) and reduce the transaction costs of coordinating shared infrastructural projects (McNamara, 1993).…”
Section: Levels Of Institutionalization and The Economic Roles Of Basmentioning
confidence: 99%
“…Indeed, management scholars have identified different effects that experience might have on performance. While some studies suggested that individuals learn from experience (Delmar and Shane, 2006; Toft‐Kehler, Wennberg and Kim, 2014), others have highlighted that experience could adversely affect performance (Betton, Branston and Tomlinson, 2019; Eggers, 2012; Simon, Houghton and Aquino, 2000). To enhance our understanding of learning from experience in the business context, scholars have turned to the study of serial entrepreneurs.…”
Section: Introductionmentioning
confidence: 99%